Chemotaxonomic Relationship of Oligomer Resveratrol in Three Malaysian Dipterocarpus Species from the Taxonomic Tribe of Dipterocarpaceae - Nawi, Liliwirianis; Zain, Wan Zuraida Wan Mohd; Ahmat, Norizan; Osman, Che Puteh; Takaya, Yoshiaki; Kamarozaman, Aisyah Salihah; Adnan, Noorazlina; Azahar, Siti Zakirah (Indonesian Journal of Chemistry, 2024)
A phytochemical investigation of three species of Malaysian Dipterocarpus contributed to the isolation of 22 compounds which consist of 15 oligostilbenoids, 2 terpenes, 2 coumarins, and 3 flavonoids. The isolation of flavonoids in the Dipterocarpaceae family is very limited. Moreover, 4-methoxepigallocatechin-3-O-O-(3-methyl) gallate (20) was isolated for the first time in the plant. The occurrence of 4-O-methylgallocatechin (18) and its stereoisomer; 4-O’-methylepigallocatechin (19) was first reported in the Dipterocarpaceae family. This study also reported the existence of several types of oligostilbenoids such as davidiol A (8), stenophyllol B (9), isohopeaphenol (11), resveratrol (1), and ampelopsin E (10) which are the first occurrence in Dipterocarpus genus and suggested a significant chemotaxonomic relationship between Dipterocarpus, more closely to Vatica which is classified under Dipterocarpeae tribe.